2006
DOI: 10.1016/j.bcp.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

3′-Azido-3′-deoxythymidine (AZT) is a competitive inhibitor of thymidine phosphorylation in isolated rat heart and liver mitochondria

Abstract: Long-term use of 3'-azido-3'-deoxythymidine (AZT) is associated with various tissue toxicities, including hepatotoxicity and cardiomyopathy, and with mitochondrial DNA depletion. AZT-5'-triphosphate (AZTTP) is a known inhibitor of the mitochondrial DNA polymerase gamma and has been targeted as the source of the mitochondrial DNA depletion. However, in previous work from this laboratory with isolated rat heart and liver mitochondria, AZT itself was shown to be a more potent inhibitor of thymidine phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 37 publications
1
48
0
1
Order By: Relevance
“…However, other research has shown that AZT is slowly phosphorylated, if at all, beyond AZTMP in many tissues [2,3,5]. Past research from this laboratory has shown that AZT competitively inhibits thymidine kinase 2 in isolated rat heart and liver mitochondria [6] and in the perfused whole rat heart [7]. In the isolated mitochondria, the K i values for inhibition of thymidine phosphorylation are 10.6 ± 4.5 μM AZT for heart mitochondria and 14.0 ± 2.5 μM AZT for liver mitochondria [6].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, other research has shown that AZT is slowly phosphorylated, if at all, beyond AZTMP in many tissues [2,3,5]. Past research from this laboratory has shown that AZT competitively inhibits thymidine kinase 2 in isolated rat heart and liver mitochondria [6] and in the perfused whole rat heart [7]. In the isolated mitochondria, the K i values for inhibition of thymidine phosphorylation are 10.6 ± 4.5 μM AZT for heart mitochondria and 14.0 ± 2.5 μM AZT for liver mitochondria [6].…”
Section: Introductionmentioning
confidence: 94%
“…Past research from this laboratory has shown that AZT competitively inhibits thymidine kinase 2 in isolated rat heart and liver mitochondria [6] and in the perfused whole rat heart [7]. In the isolated mitochondria, the K i values for inhibition of thymidine phosphorylation are 10.6 ± 4.5 μM AZT for heart mitochondria and 14.0 ± 2.5 μM AZT for liver mitochondria [6]. This suggests that AZT inhibits thymidine phosphorylation much more readily than AZTTP inhibits polymerase γ.…”
Section: Introductionmentioning
confidence: 95%
“…[28][29][30] Apart from their direct effect on mtDNA polymerase γ, nucleoside analogues may also compete with endogenous nucleosides for phosphorylation by mitochondrial thymidine kinase 2 and also for transport into the mitochondria. 31,32 Evidence is now emerging that NRTIs may increase the rate of accumulation of mtDNA mutations, and increased mutations have been demonstrated longitudinally in peripheral leukocytes in Figure 1: Selected endogenous nucleosides and their corresponding antiviral drug analogues patients on HAART. 33 In addition, Maagaard et al found increased mtDNA deletions in the skeletal muscle of patients exposed to NRTIs, 34 and reduced mitochondrial gene expression has been demonstrated in adipocytes exposed to NRTIs.…”
Section: Introductionmentioning
confidence: 99%
“…AZT is a well-known anti-HIV drug of nucleoside reverse transcriptase class, used as one of the main drug components of highly active anti-retroviral therapy (HAART). The toxic influences on mitochondria are widely described: AZT depleted mitochondrial DNA in isolated rat liver and heart mitochondria, 15 caused dysfunction of mitochondrial respiratory chain, leading to anaerobic ATP synthesis and lactic acid production, 16 histopathological and ultrastructural changes of mitochondria, 17 and oxidative stress by activation of reactive oxygen species. 18 These events are considered as the main causes leading to severe side effects such as hepatotoxicity, 19 cardiac and skeletal muscle pathologies, peripheral neuropathy, pancreatitis, lactic acidosis, and bone marrow suppression.…”
Section: Introductionmentioning
confidence: 99%